Wild meat hunting levels and trade in a West African protected area in Togo - Sonhaye-Ouyé, A.; Hounmavo, A.; Assou, D.; Afi Konko, F.; Segniagbeto, G.H.; Ketoh, G.K.; Funk, S.M.; Dendi, D.; Luiselli, L.; Fa, J.E. (Wiley, 2022)
We assessed numbers and biomass of species hunted and sold for wild meat in 12 park-adjacent settlements in the Fazao Malfakassa National Park (FMNP), Togo. From hunter interviews and market carcass counts, 33 species, 28 from hunter interviews and 26 from market surveys were taken, respectively. A total of 2605 animals were recorded in the study, 18 species during the wet season (740 animals) and 26 species in the dry season (1865 animals). In markets, 754 carcasses of 19 species were traded during the wet season, and 1896 carcasses of 24 species in the dry season. Most species were relatively small-bodied mammals (62% of total numbers of animals reported), the rest large ungulates. Species were generally of minor conservation concern (LC or NT) with only three EN and NE. From the gathered field data, we estimated that an average of 9095 ± 5613 animals per study village were hunted per year, amounting to a biomass of 198,334 ± 191,930 kg. Despite efforts to protect the wildlife within the FMNP, reported level of hunting, particularly of large ungulates within the park, the reported level of hunting is likely to have severe consequences on the long-term viability of this important protected area.